Pengelolaan Pembelajaran Jarak Jauh Yang Memandirikan Siswa dan Implikasinya pada Pelayanan Pendidikan - Nindiati, Dina Sri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study is to formulate the management of distance learning that sets students apart and their implications for the services that educational institutions must perform. The study was conducted using the literature review method using the content analysis method. Literature review method that uses various references such as books, research journals, and distance learning management modules that are applied to educational institutions. The results of the research indicate that the implementation of distance learning must be managed systematically starting from the preparation of the syllabus of the material, the selection of learning activities, and learning strategies. formulate the structure of the material and choose relevant activities, while the assignments given must consider the burden, time, and ability of students. Conclusions, Educational institutions need to seek effective and efficient communication services, supervision, and assistance to students and parents. Keywords: Distance Learning, Student Independence, Education Services